2018
DOI: 10.1007/s11103-018-0758-1
|View full text |Cite
|
Sign up to set email alerts
|

A 22-bp deletion in OsPLS3 gene encoding a DUF266-containing protein is implicated in rice leaf senescence

Abstract: Key message The OsPLS3 locus was isolated by map-based cloning that encodes a DUF266-containing protein. OsPLS3 regulates the onset of leaf senescence in rice. Glycosyltransferases (GTs) are one of the most important enzyme groups required for the modification of plant secondary metabolites and play a crucial role in plant growth and development, however the biological functions of most GTs remain elusive. We reported here the identification and characterization of a novel Oryza sativa premature leaf senescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Although several studies have uncovered functions for O-glycosylation in many key cellular processes (Zentella et al, 2016; Xu et al, 2017; Zentella et al, 2017), very few have been functionally related to senescence in plants. Taken with the findings by Li et al (Li et al, 2018), it has been suggested that protein O-glycosylation modification might plays an important role in leaf senescence.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Although several studies have uncovered functions for O-glycosylation in many key cellular processes (Zentella et al, 2016; Xu et al, 2017; Zentella et al, 2017), very few have been functionally related to senescence in plants. Taken with the findings by Li et al (Li et al, 2018), it has been suggested that protein O-glycosylation modification might plays an important role in leaf senescence.…”
Section: Discussionsupporting
confidence: 69%
“…Its deduced amino acid sequence displays a high similarity to acetylglucosaminyl transferases family involved in protein O -glycosylation modification. During preparing for this article, Li et al (Li et al, 2018) published premature leaf senescence mutant ( ospls3 ). There are similarities between psl and ospls3 mutants in many respects, including the increased level of ethylene.…”
Section: Discussionmentioning
confidence: 99%
“…Equally importantly, the functions of some DUF genes are diverse and complex, as mentioned earlier in DUF538 genes. For instance, it is reported that a gene containing DUF266 is involved in leaf senescence in addition to the previously mentioned role related to cell wall development [ 44 ]. The study found the DUF266-containing gene OsPLS3 plays an important role in the onset of leaf senescence through perturbing ethylene production in leaves, thereby affecting the onset of leaf senescence in rice.…”
Section: Role Of Dufs In Plant Growth and Developmentmentioning
confidence: 99%